Utilization of Bacterial Cellulose of Nata de Soya as an Alternative Raw Material for Honeycomb Paper Wrap - Azis, Denisda Nabhan; Aziza, Sharfina Rani; Puspitaningtyas, Isnania; Putra, Mohammad Syafiq Alika; Margono, Margono (Equilibrium Journal of Chemical Engineering, 2025)
ABSTRACT. The growing production of wood-based paper has contributed to deforestation and environmental pollution, underscoring the urgent need for alternative, sustainable raw materials. Bacterial cellulose derived from nata de soya presents a promising non-wood source for paper production. This study investigated the utilization of bacterial cellulose from nata de soya as a raw material for honeycomb paper wrap applications. Bacterial cellulose obtained from 18-day-old nata de soya was processed into paper with the addition of kaolin and tapioca as functional additives. Four formulations were evaluated: Formula 1 (100% bacterial cellulose), Formula 2 (62% bacterial cellulose and 38% kaolin), Formula 3 (76% bacterial cellulose and 24% tapioca), and Formula 4 (52% bacterial cellulose, 32% kaolin, and 16% tapioca). The resulting papers were characterized in terms of thickness, grammage, moisture content, tensile strength, and load-bearing capacity. The results demonstrated that Formula 4 exhibited the most favorable performance, with a thickness of 0.43 mm and a grammage of 191 g/m², complying with packaging paper standards (SNI 8218:2015). The moisture content was 5.66%, within the acceptable limit specified by SNI 7274:2008, and the tensile strength reached 1.659 kN/m, exceeding the minimum standard requirement. Furthermore, the honeycomb paper wrap produced using Formula 4 showed a load-bearing capacity comparable to that of commercial products. These findings indicate that bacterial cellulose paper formulated with a combination of kaolin and tapioca has strong potential as a sustainable alternative material for honeycomb paper wrap.Keywords:Bacterial cellulose, Deforestation, Honeycomb paper wrap, nata de soya, Tofu wastewater